Agricultural and trade policy reform and inequality: The distributive effects of direct payments to German farmers under the EU's new common agricultural policy - Harald von Witzke; Steffen Noleppa (Humboldt-Universität zu Berlin, Wirtschafts- und Sozialwissenschaften an der Landwirtschaftlich-Gärtnerischen Fakultät, 2007)
The Common Agricultural Policy (CAP) of the European Union has been in a process of reform since the early 1990s. As a result of reforms, agricultural market regulations have become more liberal and direct payments have been introduced which are to a large extent decoupled from production. In this paper, we analyze the effects of the direct payments to farmers on inequality of profits in German agriculture. For this purpose, we decompose measures of absolute and relative inequality in total farm profits into the partial effects of the direct payments and all other profit determinants. Key results of the analysis are that the system of direct payments under the New CAP accounts for about one third of the observed inequality in family farms and for almost two thirds of inequality in the large incorporated farms.
Keywords: D31; Q12; Q18; 330; Common Agricultural Policy; agricultural subsidies; income distribution; decoupled payments